PERLINDUNGAN HUKUM TERHADAP TERSANGKA ANAK SEBAGAI UPAYA MELINDUNGI HAK ANAK - Mahfiana, Layyin (IAIN Pekalongan, 2011)
Abstract: Any activities conducted within. Juvenile justice process, should be based on a principle, for the welfare, interests and future. front of them, of course, without, reducing attention to the interests of society. So when the child becomes a suspect protection is needed, which not only juridical but also non-juridical, which includes protection in the social, health, and education. It dimaksdukan to ensure children's rights as the nation's future generations.